2011
DOI: 10.1073/pnas.1102302108
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection by female immunity against paternal antigens can fix loss of function alleles

Abstract: Humans lack the common mammalian cell surface molecule N-glycolylneuraminic acid (Neu5Gc) due to a CMAH gene inactivation, which occurred approximately three million years ago. Modern humans produce antibodies specific for Neu5Gc. We hypothesized that anti-Neu5Gc antibodies could enter the female reproductive tract and target Neu5Gc-positive sperm or fetal tissues, reducing reproductive compatibility. Indeed, female mice with a human-like Cmah(−/−) mutation and immunized to express anti-Neu5Gc antibodies show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 33 publications
2
92
0
Order By: Relevance
“…With respect to fertility, it has been suggested that antibodies within the uterine environment may impair fertility by two potential mechanisms including sperm inactivation and embryo rejection or failed implantation secondary to incompatibility between the blastocyst and receptive uterus [22]. Our results reveal a lower CPR in the presence of anti-Neu5Gc antibodies within the uterine environment.…”
Section: Uterine Lavage Neu5supporting
confidence: 29%
See 1 more Smart Citation
“…With respect to fertility, it has been suggested that antibodies within the uterine environment may impair fertility by two potential mechanisms including sperm inactivation and embryo rejection or failed implantation secondary to incompatibility between the blastocyst and receptive uterus [22]. Our results reveal a lower CPR in the presence of anti-Neu5Gc antibodies within the uterine environment.…”
Section: Uterine Lavage Neu5supporting
confidence: 29%
“…endometriosis, auto-immune diseases, tubal infertility) [20,21]. It has recently been suggested, that the loss of Neu5Gc may have caused reproductive incompatibility in ancestral hominin populations due to sexual selection by female immunity against the xenoglycan Neu5Gc on sperm or implanting blastocysts [22]. In a murine model, Cmah null females with antibodies against Neu5Gc have reduced fertility when mated with Neu5Gc positive wild-type males implicating that female immunity can result in reproductive incompatibility [22].…”
Section: Introductionmentioning
confidence: 99%
“…CMAH enzyme produces N-glycolylneuraminic acid (Neu5Gc) derived from N-acetylneuraminic acid (Neu5Ac) through enzymatic hydroxylation [1] . Neu5Gc and Neu5Ac are two of the most abundant sialic acids and both of them are expressed in echinoderm to mammalians [1][2][3][4] . These sialic acids have significant biologic roles in cellular recognition, signaling, neuronal development, and host-pathogen interaction in vertebrates, including humans [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Female mice genetically engineered with a human-like Cmah Ϫ/Ϫ mutation and immunized to express ␣-Neu5Gc antibodies show reduced fertility when mated with Neu5Gc-positive wild type males (13,24). Furthermore, human ␣-Neu5Gc antibodies are also capable of targeting paternally derived antigens and can mediate cytotoxicity against Neu5Gc-bearing chimpanzee sperm in vitro (13), (37). Here, we investigate the possible consequences of the presence of Neu5Gc and ␣-Neu5Gc antibodies in the reproductive system in a mouse model humanized for its sialic acid and ␣-xenoglycan immune response.…”
mentioning
confidence: 99%
“…It has been proposed that circulating anti-sialic acid antibodies target incorporated non-human sialic acid and contribute to chronic inflammation in various tissues (10 -12). Our objective is to determine whether xenoglycan-antibody interactions also affect human infertility (13) given tentative evidence from a clinical study (14). Sialic acids (Sias) are nine-carbon backbone, acidic, amino sugars that decorate the surfaces of all vertebrate cells in high abundance (tens to hundreds of millions of molecules per cell).…”
mentioning
confidence: 99%